Local Culture-Based Tourism Development Strategy in Madura Regency: Potential and Challenges - Achmad Wahyudi; Kristyan Dwijosusilo; Ika Devy Pramudiana; Sri Roekminiati; Sapto Pramono (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2024)
Tourism based on local culture in Madura Regency has great potential in supporting economic growth and cultural preservation. This study aims to analyze the impact of local culture-based tourism development on community welfare (SDGs Goal 8) and cultural sustainability (SDGs Goal 11). The method used is a qualitative descriptive approach with thematic data analysis from in-depth interviews, observations, and literature studies. The results of the study show that the development of tourism based on local culture creates new economic opportunities, such as an increase in employment of up to 20%, an increase in community income of 15%, and local participation of up to 40%. In addition, tourism also plays an important role in the preservation of cultural traditions, with an increase in the number of annual cultural festivals and the preservation of cultural sites by up to 15%. However, challenges such as low public education and the threat of modernization require a comprehensive management strategy. With collaboration between the government, the community, and business actors, the development of local culture-based tourism in Madura can continue to provide economic benefits while preserving cultural heritage. This research provides recommendations to strengthen community training, improve tourism promotion, and utilize digital technology in the preservation of local culture